Formulasi Sediaan Tablet Kunyah Kompleks Inklusi Dimenhidrinat–β-Siklodekstrin dengan Metode Pengeringan Semprot (Chewable Tablet from Inclusion Complexes of Dimenhydrinate– β-Cyclodextrine using Spray Drying Method) - Faizatun, Faizatun; Joenoes, Luvita; Nafisa, Safira (Indonesian Research Gateway, 2019)
Taste becomes an important parameter in the delivery of a chewable tablet, primarily aimed for childrens. The purpose of this study is to mask the bitter taste and create dimenhydrinate chewable tabletas motion sickness drug that meet the physical and chemical quality. The method used to mask the bitter taste of dimenhydrinate is inclusion complexes with β-cyclodextrin in spray drying. Inclusion complex powders evaluation included flowcity and water content, and characterized by infrared spectrophotometry and DSC (Differential Scanning Calorimetry). Inclusion complex powders was made into chewable tablet with direct compression method. Chewable tablet was evaluated including tablets concentration (94.33-106,47%), the diversity of weights (85-115%), tablets diameter (1.013 cm), tablets thickness (0.49 cm), hardness (3.75-4.58 kg/cm2), friability (2,98-3,42%,). Dimenhydrinate chewable tablet taste test were statistically analyzed with non-parametric Kruskal-Wallis which results a significant differences of the bitter taste that masked among the five molar concentration differences of dimenhydrinate and β-cyclodextrine. The higher molar ratio of β-cyclodextrin (0,5-3) used, has the better result for masking the bitterness of dimenhydrinate. The used of β-cyclodextrin with the ratio in five molar concentration differences can not optimally mask the bitter taste of dimenhydrinate. Chewable tablet of formula IV has met the best physical and chemical quality. Taste becomes an important parameter in the delivery of a chewable tablet, primarily aimed for childrens. The purpose of this study is to mask the bitter taste and create dimenhydrinate chewable tabletas motion sickness drug that meet the physical and chemical quality. The method used to mask the bitter taste of dimenhydrinate is inclusion complexes with β-cyclodextrin in spray drying. Inclusion complex powders evaluation included flowcity and water content, and characterized by infrared spectrophotometry and DSC (Differential Scanning Calorimetry). Inclusion complex powders was made into chewable tablet with direct compression method. Chewable tablet was evaluated including tablets concentration (94.33-106,47%), the diversity of weights (85-115%), tablets diameter (1.013 cm), tablets thickness (0.49 cm), hardness (3.75-4.58 kg/cm2), friability (2,98-3,42%,). Dimenhydrinate chewable tablet taste test were statistically analyzed with non-parametric Kruskal-Wallis which results a significant differences of the bitter taste that masked among the five molar concentration differences of dimenhydrinate and β-cyclodextrine. The higher molar ratio of β-cyclodextrin (0,5-3) used, has the better result for masking the bitterness of dimenhydrinate. The used of β-cyclodextrin with the ratio in five molar concentration differences can not optimally mask the bitter taste of dimenhydrinate. Chewable tablet of formula IV has met the best physical and chemical quality. Taste becomes an important parameter in the delivery of a chewable tablet, primarily aimed for childrens. The purpose of this study is to mask the bitter taste and create dimenhydrinate chewable tabletas motion sickness drug that meet the physical and chemical quality. The method used to mask the bitter taste of dimenhydrinate is inclusion complexes with β-cyclodextrin in spray drying. Inclusion complex powders evaluation included flowcity and water content, and characterized by infrared spectrophotometry and DSC (Differential Scanning Calorimetry). Inclusion complex powders was made into chewable tablet with direct compression method. Chewable tablet was evaluated including tablets concentration (94.33-106,47%), the diversity of weights (85-115%), tablets diameter (1.013 cm), tablets thickness (0.49 cm), hardness (3.75-4.58 kg/cm2), friability (2,98-3,42%,). Dimenhydrinate chewable tablet taste test were statistically analyzed with non-parametric Kruskal-Wallis which results a significant differences of the bitter taste that masked among the five molar concentration differences of dimenhydrinate and β-cyclodextrine. The higher molar ratio of β-cyclodextrin (0,5-3) used, has the better result for masking the bitterness of dimenhydrinate. The used of β-cyclodextrin with the ratio in five molar concentration differences can not optimally mask the bitter taste of dimenhydrinate. Chewable tablet of formula IV has met the best physical and chemical quality.